Pearl Raising in Guangxi Province and Its Importance to the Local Economy - Yangming, Wang; Laoakka, Sastra; Yodmalee, Boonsom (Thai Journal of East Asian Studies, 2018)
This research adopted a cultural qualitative research method and had three aims: (a) to study the background of pearl raising in Guangxi Province, People’s Republic of China; (b) to study the current conditions and problems with pearl raising in Guangxi Province, People’s Republic of China; and (c) to study pearl raising and its effects on the economy of Guangxi Province, People’s Republic of China. The research area was selected using a purposive sampling method and three sample groups were chosen to provide data for the investigation: six key informants, six casual informants and 68 general informants. Data was collected by observations, interviews, focus group discussions and a workshop. All collected data was validated using a triangulation method and the results are presented here as a descriptive analysis. The results show that China is considered a world leader in the cultivation and production of pearls. Pearls are white, pink and gold gemstones derived from oysters and may be considered the only gemstones to come from animals. The environmental conditions for pearl raising are crucial because any variation may have a disastrous effect on the oysters. Current problems with the pearl industry in Guangxi Province come from a lack of knowledge and understanding of technology. Pearl oysters are animals that have a positive effect on the economy by creating jobs and generating income. They thus have a huge economic and commercial value to the people of Guangxi Province, People’s Republic of China.